2017
DOI: 10.1212/nxi.0000000000000358
|View full text |Cite
|
Sign up to set email alerts
|

Comparative utility of disability progression measures in PPMS

Abstract: Objective:To assess the comparative utility of disability progression measures in primary progressive MS (PPMS) using the PROMiSe trial data set.Methods:Data for patients randomized to placebo (n = 316) in the PROMiSe trial were included in this analysis. Disability was assessed using change in single (Expanded Disability Status Scale [EDSS], timed 25-foot walk [T25FW], and 9-hole peg test [9HPT]) and composite disability measures (EDSS/T25FW, EDSS/9HPT, and EDSS/T25FW/9HPT). Cumulative and cross-sectional unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Interestingly, this corresponds, using the same combined endpoint, to the reported 2-year cumulative confirmed disease progression rate of 56.7% in the placebo cohort of the PPMS patients in the PROMiSe trial. 15 However, the confirmed disease progression rate in our trial for the placebo group was only 38.2%, which in our design approached the anticipated 30% progression rate for the fluoxetine group. Given the unexpected slow rate of progression in the placebo arm, there is insufficient statistical power to detect a potential treatment effect of fluoxetine.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…Interestingly, this corresponds, using the same combined endpoint, to the reported 2-year cumulative confirmed disease progression rate of 56.7% in the placebo cohort of the PPMS patients in the PROMiSe trial. 15 However, the confirmed disease progression rate in our trial for the placebo group was only 38.2%, which in our design approached the anticipated 30% progression rate for the fluoxetine group. Given the unexpected slow rate of progression in the placebo arm, there is insufficient statistical power to detect a potential treatment effect of fluoxetine.…”
Section: Discussionmentioning
confidence: 40%
“…Adding the traditional EDSS to the composite endpoint might have led to the registration of more progression events. 15 However, we decided not to include the EDSS because clinical assessments were performed by study nurses visiting the patients at their home. The study nurses were well trained to assess the T25-FW and 9-HPT but not to perform and register the EDSS.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent analysis of data from the placebo arm of the PROMiSe trial, which was conducted in patients with primary progressive MS [ 49 ], sustained (3-month) worsening of the EDSS was less sensitive to disability progression than sustained (3-month) changes in the T25FW (≥ 20% increase) or composite measures (EDSS or T25FW; EDSS or 9HPT [≥ 20% increase]; EDSS, T25FW or 9HPT). The authors concluded that T25FW or composite measures should be considered as the primary endpoint for future studies of new disease-modifying therapies [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent modeling of the trial's database supported the use of composite endpoints to include patients evidencing a 12-week 20% sustained change from baseline for the timed 25-foot walk test (T25FWT), or 9-hole peg test (9HPT), or CDP based on EDSS as a full set, or paired sets compared to the standard CDP by EDSS alone; comparisons were also done for more stringent 24-week CDP. 19 Others have explored the power of these endpoints as well; 20 but to date, these composite outcomes have not been explored by baseline patient characteristics that might improve the outcome sensitivity by study enrichment.…”
Section: Introductionmentioning
confidence: 99%